Auto-Reactive Th17-Cells Trigger Obsessive-Compulsive-Disorder Like Behavior in Mice With Experimental Autoimmune Encephalomyelitis - Kant, Ravi; Pasi, Shweta; Surolia, Avadhesha (Frontiers in Immunology, 2018)
Th17-lymphocytes are well known for their deleterious role in autoimmunity. But does the notoriety of this repertoire extend beyond autoimmunity? In the present study we employed experimental autoimmune encephalomyelitis as model system to study the role auto-reactive Th17 cells in neuropsychiatric disorders. The mice with experimental autoimmune encephalomyelitis exhibited exaggerated grooming activity. The observed behavioral anomaly resembled obsessive compulsive disorder (OCD) upon analysis of grooming microstructure, induced grooming, marble burying and nestlet shredding. The observed OCD like behavior was relieved upon Th17 cell depletion; alternatively, it could alone be induced by adoptive transfer of myelin oligodendrocyte glycoprotein (35-55) reactive Th17 in B6.Rag1-/- mice. The observed OCD like behavior was also alleviated upon treatment with a selective serotonin reuptake inhibitor, fluoxetine.